Excursions in Harmonic Analysis, Volume 4 The February Fourier Talks at the Norbert Wiener Center - Balan, Radu; Begué, Matthew; Benedetto, John J.; Czaja, Wojciech; Okoudjou, Kasso A. (Applied and Numerical Harmonic Analysis, 2015)
This volume consists of contributions spanning a wide spectrum of harmonic analysis and its applications written by speakers at the February Fourier Talks from 2002 - 2013. Containing cutting-edge results by an impressive array of mathematicians, engineers, and scientists in academia, industry, and government, it will be an excellent reference for graduate students, researchers, and professionals in pure and applied mathematics, physics, and engineering. Topics covered include:   • Special Topics in Harmonic Analysis • Applications and Algorithms in the Physical Sciences • Gabor Theory • RADAR and Communications: Design, Theory, and Applications   The February Fourier Talks are held annually at the Norbert Wiener Center for Harmonic Analysis and Applications. Located at the University of Maryland, College Park, the Norbert Wiener Center provides a state-of- the-art research venue for the broad emerging area of mathematical engineering.